2021
DOI: 10.1016/j.ssaho.2021.100201
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic analysis of neologism related to coronavirus (COVID-19)

Abstract: The current study aimed to explore the linguistic analysis of neologism related to Coronavirus (COVID-19). Recently, a new coronavirus disease COVID-19 has emerged as a respiratory infection with significant concern for global public health hazards. However, with each passing day, more and more confirmed cases are being reported worldwide which has alarmed the global authorities including the World Health Organization (WHO). In this study, the researcher uses the term neologism which means the coinage of new w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 2 publications
0
26
0
3
Order By: Relevance
“…Thereupon, related to the word-formation processes, all types of word-formation processes were not fully involved in the creation of neologisms from the perspective of COVID-19 (Asif, Zhiyong, Iram, & Nisar, 2020). On the other hand, new English words collected in this research all involve word-formation.…”
Section: Discussionmentioning
confidence: 74%
“…Thereupon, related to the word-formation processes, all types of word-formation processes were not fully involved in the creation of neologisms from the perspective of COVID-19 (Asif, Zhiyong, Iram, & Nisar, 2020). On the other hand, new English words collected in this research all involve word-formation.…”
Section: Discussionmentioning
confidence: 74%
“…English has many word-formation devices for constructing new words from existing ones, such as compounding, blending, clipping, acronyms, abbreviation, conversion, affixation, back-formation, and borrowing (Bauer, 1983;Yule, 2020). There is a relatively small body of literature concerned with providing a linguistic analysis of word-formation processes involved in constructing new terms related to COVID-19 (Al-Salman & Haider, 2021;Asif et al, 2021;Fitria, 2021;Goltsova & Chybis, 2021). Akut (2020) and Asif et al (2021) found that most neologisms related to COVID-19 are nouns.…”
Section: Studies On Word-formation Processes Related To Covid-19mentioning
confidence: 99%
“…The term "coronavirus" consists of two words: corona, which means "crown," and virus (Al-Salman & Haider, 2021;Asif, Zhiyong, Iram, & Nisar, 2021;Thorne, 2020). In January 2020, the WHO started to call this type of coronavirus COVID-19 (i.e., coronavirus disease 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Asif, et al (2021), neologisms present colorful portrayals of various social and cultural practices of respective societies. Similarly in this study, some neologisms were derived from socio-cultural lexicons.…”
Section: Sample # 22 It Was a Dispute Between Warring Clans Here A Century's Old Practice Calledmentioning
confidence: 99%